Green, pervasive, and cloud computing : 12th International Conference, GPC 2017, Cetara, Italy, May 11-14, 2017, Proceedings /: 12th International Conference, GPC 2017, Cetara, Italy, May 11-14, 2017, Proceedings. (2017) - Unknown
No abstract available